2020
DOI: 10.13075/ijomeh.1896.01513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of molecular markers as IL-12, IL-22 and IFN-γ in correlation with a clinical course in patients with psoriasis

Abstract: As a chronic, recurrent, immunologically mediated systemic disease and a common cause of dermatological problems, psoriasis is often a subject of scientific research. Skin changes located on the hands can cause difficulties and limitations in the performance of professional activities, especially manual ones. The main role in pathogenesis is played by immunological factors-improper functioning of the components of the immune system, among others, T lymphocytes and cytokines like interleukin-12 (IL-12), interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Isolation of total RNA from T-regulatory cells and skin homogenates was performed using the mirVana™ miRNA Isolation Kit (Life Technologies, Carlsbad, CA, USA), which provides efficient isolation of small RNA-containing total RNA. This kit is compatible with virtually all cell and tissue types, and has been used previously to isolate RNA from body fluids and tissues [42][43][44]. Isolation of total RNA was carried out following the manufacturer's recommendations.…”
Section: Rna Isolation Qualitative and Quantitative Rna Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of total RNA from T-regulatory cells and skin homogenates was performed using the mirVana™ miRNA Isolation Kit (Life Technologies, Carlsbad, CA, USA), which provides efficient isolation of small RNA-containing total RNA. This kit is compatible with virtually all cell and tissue types, and has been used previously to isolate RNA from body fluids and tissues [42][43][44]. Isolation of total RNA was carried out following the manufacturer's recommendations.…”
Section: Rna Isolation Qualitative and Quantitative Rna Evaluationmentioning
confidence: 99%
“…The evaluation of gene expression was performed analogously to the previously described procedure [44]. The reverse transcription (RT) reaction was performed using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Carlsbad, CA, USA) in a volume of 20 µL.…”
Section: Evaluation Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research showed that immune and inflammatory mechanisms play essential roles in psoriatic pathogenesis. [ 15 ] Especially, pathogenic T cell subsets such as Th1, Th17, Th22 and their characteristic cytokines including IFN-γ, IL-1β, IL-6, TNFα, IL-17, IL-23, chemokines and so on form the immune network of psoriasis through complex signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of IL-22 on keratinocytes was highlighted through overexpression of IL-22 receptor (IL-22R) in the epidermis of psoriatic skin compared to that of normal skin [ 120 ]. Studies revealed that upregulation of IL-22, along with IL-12B and IFN-γ in the psoriatic skin, is involved in the initiation and sustenance of the disease [ 121 ]. A GWAS identified the IL-22 association with psoriasis in the Japanese [ 122 ].…”
Section: Psoriasis and Non-mhc Genesmentioning
confidence: 99%